A Culturally Responsive Curricular Revision to Improve Engagement and Learning in an Undergraduate Microbiology Lab Course - Fuller, Karla S.; Torres Rivera, Camila (Frontiers in Microbiology, 2021)
We seek to increase student engagement and success to subsequently lead to increased retention and degree attainment for students at our Hispanic-serving institution. We hypothesized that using a culturally responsive approach in an undergraduate microbiology lab would increase engagement and learning gains. Using a culturally responsive approach allowed students to start their learning from their own place of understanding – centering students’ lived experiences. Students interviewed family members to learn about “home remedies,” and then devised experiments to test whether those home remedies affected growth of bacteria commonly implicated in gastrointestinal distress (Staphylococcus aureus, Bacillus cereus, and Escherichia coli) or sore throat (Neisseria gonorrhoeae, Streptococcus pyogenes, and Mycoplasma pneumoniae). As a final assessment, students generated project posters which they presented at a class symposium. Implementation of a culturally responsive research experience focused on the gut microbiome resulted in increased learning gains as evidenced by movement up Bloom’s revised taxonomy scale. Student feedback indicated increased engagement, increased confidence in communicating science and a deeper understanding and appreciation for microbiology. Taken together, the results indicate that students appreciate a more culturally responsive and student-centered approach to learning in microbiology and encourages expansion of this approach to other modules in the course. This paper includes responsive data to support this claim, as well as a sample course calendar and supplementary learning material to support the human microbiome approach to microbiology.